ANALISIS HUBUNGAN KELEMBAGAAN ANTARA OTORITAS JASA KEUANGAN DENGAN BANK INDONESIA - BISDAN SIGALINGGING (USU LAW JOURNAL, 2013)
The characteristic of OJK institution is independent to realize national economy which growth sustainably, especially in regulate and supervise banking sector. OJK has coordination with other institutions by integrated, independent, just, transparent, and accountable inter financial institution. How is the independency of OJK and BI in regulating and supervise banks, and how is the coordinating relationship between OJK and BI? The type of the research was judicial normative. The independency of OJK and BI is very different. The independency of OJK in its regulation has governmental element, but independency of BI does not. It can spoil the principle of the philosophy independency. Coordinating between OJK and BI can be established through cooperation in making regulation and supervise banks, specially in handling micro-prudential. In the abnormal condition, the coordinating is made through FKSSK for the handling of macro-prudential. It is recommended that regulating independency unmistakable if want to maintained independency, ex officio should be omitted because it will spoil the independency principle, or, if ex officio is used, the independency of OJK should be eliminated. BI and OJK should make standard guidance of the technical of coordination to anticipate the overlapping of the implementation of task and responsibility. Keywords: Independency, Authority of Financial Service, Bank Indonesia